Can you please help me? :))
![Can you please help me class=](https://us-static.z-dn.net/files/d6b/f4460a63336f7b56aace711599757097.png)
Answer:
9/2
Step-by-step explanation:
(6x^-2)^2 (0.5x)^4
= 6^2 x^-4 * (1/2)^4 x^4
= 36/16 * x^0
= 9/2 * 1
= 9/2
Answer:
Step-by-step explanation:
Rewrite the expression using the negative exponent rule. (b^-n=1/b^n
(6 1/x^2) Do this by writing 6 as a fraction with a denominator of 1. Then, multiply 6/1 and 1/x^2.
Apply the product rule to 6/x^2 ... (6^2 / x^2)^2(0.5x)^4
Raise 6 to the power of 2. ... 36/(x^2)^2(0.5x)
Multiply the exponents in (x^2)^2. You get: 36/x^4(0.5x)^4
Apply the product rule to 0.5x. You get: 36/x^4(0.5^4x^4) and cancel the common factors. (the common factor is x^4)
You would get: 36/1 and 0.5^4/1.
After simplifying, it would equal 2.25/1.
Which is 2.25.
Mark branliest?